Regards artistiques sur l’observation photographique - Frédérique Mocquet (Projets de Paysage)
Bertrand Stofleth and Geoffroy Mathieu place at the heart of their personal practice the representation of the territory and changes in contemporary landscapes. In 2005 they paired up as Les Panoramistes, combining their perspectives to produce the Photographic Observatories of the Landscape. After having created the Monts d’Ardèche Regional Nature Park Photographic Observatory of the Landscape and the Photographic Observatory of the Landscape of the grouping of municipalities of the Hérault Valley, in 2012 they created “Used Landscapes, The Photographic Observatory of the Landscape from the GR2103 Trail”. The observatory follows and documents the GR2013 trail and its landscapes, it also offers a reinterpretation of the method adopted by the national programme of the Observatory. After having proposed a critical analysis of the photographic observation method in the article entitled “L’Observatoire photographique national du paysage : transformations d’un modèle et hypothèses renouvelées de paysage” ("The National Photographic Observatory of the Landscape : Transformations of a Model and Renewed Landscape Hypotheses”) published in the special section of this issue, the need to present a transcription of the statements of the photographers became apparent. The interview conducted on May 12th, 2016 first addressed the general issue of the photographic representation of landscapes before presenting the historical background and commitments of the GR2013 Photographic Observatory of the Landscape.